Oncolytic parvoviruses as cancer therapeutics - Rommelaere, Jean; Geletneky, Karsten; Angelova, Assia L.; Daeffler, Laurent; Dinsart, Christiane; Kiprianova, Irina; Schlehofer, Jörg R.; Raykov, Zahari Zahariev (Cytokine & growth factor reviews, 2010)
The experimental infectivity and excellent tolerance of some rodent autonomous parvoviruses in humans, together with their oncosuppressive effects in preclinical models, speak for the inclusion of these agents in the arsenal of oncolytic viruses under consideration for cancer therapy. In particular, wild-type parvovirus H-1PV can achieve a complete cure of various tumors in animal models and kill tumor cells that resist conventional anticancer treatments. There is growing evidence that H-1PV oncosuppression involves an immune component in addition to the direct viral oncolytic effect. This article summarizes the recent assessment of H-1PV antineoplastic activity in glioma, pancreatic ductal adenocarcinoma, and non-Hodgkin lymphoma models, laying the foundation for the present launch of a first phase I/IIa clinical trial on glioma patients.
Gesehen am 15.06.2023